PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 3 TELUK RHU - Senin Senin; Otang Kurniaman; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by low learning outcomes of sciencestudents. before the research the average value of science learning outcomes of thirdgrade students of SDN 3 is 69.3. The unfinished student is 15 people with minimalcriteria of completeness (KKM) which is valid is 70. This research is a classroom actionresearch (PTK) which carried out two cycles. The study was conducted in March-April,exactly enough semester 2016/2017 with the subject of research as many as 28 people.This study was conducted with the aim to improve the average score of science learningoutcomes of third grade students of SD Negeri 3 Teluk Rhu through the application ofSTAD Cooperative Type learning model. Instrument of research data collecting consistof learning device and observation sheet of teacher activity and student activity. Thedata of the research were analyzed by using statistical analysis including teacheractivity data and student activity and student learning result data. The data of teacherand student activity is obtained from the observation result score by the observer duringthe research. Student learning outcomes data obtained from students' daily test resultsat the end of each cycle. Based on the score of teacher activity and student activity, theimprovement is as follows: teacher activity in the first cycle of learning I is 54,17%, atthe end of cycle II learning increased to 91,67%. Student activity in the first learningcycle I was 41.67%, in the second cycle increased to 83.33%. Results of data analysis ofstudent learning outcomes showed an increase from the average score of 69.32 in theinitial score, increased to 80.18 on the results of daily test cycle II. The number ofstudents who completed before the implementation of the study only 13 people, on cycleII all the students as many as 28 people have been completed. This shows that theapplication of STAD type cooperative learning model can improve science learningoutcomes of third grade students of SD Negeri 3 Teluk Rhu.Keywords: STAD type cooperative learning model, science learning outcomes